KONSEP EPISTEMOLOGI IBN HAZM - Syahril Syahril (Hunafa: Jurnal Studia Islamika, 2007)
Ibn Hazm is one of Muslim thinkers who is famous for his philosophical thoughts. One of his philosophical thoughts is concerned with epistemology of science. In his view, the truth of science can be obtained through reason and senses.  Senses can comprehend the real objects while reason comprehend the abstract ones. He asserts, however, that reason faculty is higher than sense faculty since the later usually makes mistakes in understanding an object. Besides, reason can be active by itself while senses activities depend much on reason.Kata Kunci: Konsep epistemologi, panca indera, akal, intuisi, Ibn Hazm